Subunit-specific agonist activity at NR2A-, NR2B-, NR2C-, and NR2D-containing N-methyl-D-aspartate glutamate receptors - Erreger, Kevin; Geballe, Matthew T.; Kristensen, Anders; Chen, Philip E.; Hansen, Kasper B.; Lee, C. Justin; Yuan, Hongjie; Le, Phuong; Lyuboslavsky, Polina N.; Micale, Nicola; Jorgensen, Lars; Clausen, Rasmus P.; et al. (AMER SOC PHARMACOLOGY EXPERIMENTAL THERAPEUTICS, 2007)
The four N-methyl-D-aspartate ( NMDA) receptor NR2 subunits (NR2A-D) have different developmental, anatomical, and functional profiles that allow them to serve different roles in normal and neuropathological situations. Identification of subunit-selective NMDA receptor agonists, antagonists, or modulators could prove to be both valuable pharmacological tools as well as potential new therapeutic agents. We evaluated the potency and efficacy of a wide range of glutamate-like compounds at NR1/NR2A, NR1/NR2B, NR1/NR2C, and NR1/NR2D receptors. Twenty-five of 53 compounds examined exhibited agonist activity at the glutamate binding site of NMDA receptors. Concentration-response relationships were determined for these agonists at each NR2 subunit. We find consistently higher potency at the NR2D subunit for a wide range of dissimilar structures, with (2S, 4R)-4-methylglutamate (SYM2081) showing the greatest differential potency between NR2A- and NR2D- containing receptors (46-fold). Analysis of chimeric NR2A/D receptors suggests that enhanced agonist potency for NR2D is controlled by residues in both of the domains (Domain1 and Domain2) that compose the bilobed agonist binding domain. Molecular dynamics ( MD) simulations comparing a crystallography- based hydrated NR1/NR2A model with a homology-based NR1/NR2D hydrated model of the agonist binding domains suggest that glutamate exhibits a different binding mode in NR2D compared with NR2A that accommodates a 4-methyl substitution in SYM2081. Mutagenesis of functionally divergent residues supports the conclusions drawn based on the modeling studies. Despite high homology and conserved atomic contact residues within the agonist binding pocket of NR2A and NR2D, glutamate adopts a different binding orientation that could be exploited for the development of subunit selective agonists and competitive antagonists.
Keywords: ACID TRANSMITTER CANDIDATES; SITE-DIRECTED MUTAGENESIS; SINGLE-CHANNEL ANALYSIS; EXCITATORY AMINO-ACIDS; NMDA-RECEPTOR; MOLECULAR-DYNAMICS; LIGAND-BINDING; RAT-BRAIN; INTERDOMAIN INTERACTIONS; XENOPUS OOCYTES